Effects of intermittent hypoxia on adipose-derived mesenchymal stem cells in protecting alveolar type II cells from injury - RuiYin Lai; SuHeng Chen; Junjie Cui; Xiaolong Liu; Yulan Li (PLoS ONE, 2026)
Adipose-derived mesenchymal stem cells (ADSCs) have demonstrated significant therapeutic effects on acute lung injury. Numerous studies have reported that preconditioning ADSCs can enhance their therapeutic efficacy. Currently, there is a lack of research on intermittent hypoxia preconditioning of ADSCs. In this study, we subjected ADSCs to intermittent hypoxic preconditioning, followed by the detection of their expressions of HIF-1α, HGF, VEGF, and IL-10. We also evaluated the therapeutic effects of ADSCs on oxidative stress and cell apoptosis in LPS-induced MLE-12 cells, and compared the outcomes resulting from different types of hypoxic preconditioning. Finally, we concluded that Intermittent hypoxia preconditioning leads to decrease in the secretion of VEGF by ADSCs compared to sustained hypoxia preconditioning; but their therapeutic effects in terms of anti-apoptosis and anti-oxidation are comparable.